Analysis of Corporate Image, Relationship Marketing, and Service Quality on Customer Satisfaction in the Purchase of Green Bean Coffee at PT. Mulya Sari Mandiri - Firhan Sudrajat; Annisa Febrina (LPPJPHKI Universitas Dehasen Bengkulu, 2026)
This study aims to analyze the influence of corporate image, relationship marketing, and service quality on the level of customer satisfaction in the process of purchasing green bean coffee at PT Mulya Sari Mandiri. The research data were collected through the distribution of questionnaires and subsequently analyzed using a quantitative approach. A total of 78 respondents participated in this study, with the sampling technique employing saturated sampling, which falls under the category of non-probability sampling. Data processing was conducted using SPSS software version 24.0 through multiple linear regression analysis techniques. The results of the analysis indicate that corporate image (X1), relationship marketing (X2), and service quality (X3) have a positive and significant effect on customer satisfaction (Y), both partially and simultaneously, in the purchase of green bean coffee at PT Mulya Sari Mandiri. Furthermore, service quality was found to be the most dominant variable contributing to customer satisfaction, indicating that improvements in service quality are directly aligned with increased customer satisfaction. Therefore, the company is advised to continuously develop and improve the quality of services provided.